What are the predictors of postconcussion syndrome after head injury in children and young adults?. Issue 2 (February 2018) - Nyberg, Carl; Fashner, Julia
Abstract : EVIDENCE‐BASED ANSWER : In children evaluated for head injury, predictors of future postconsussion syndrome include older age, headache, delayed onset of symptoms, previous concussion, history of mood disorder, family history of migraine or mental illness, and markers of severity of injury such as need for analgesics, performance of head computed tomography (CT), and hospital admission (SOR: B, cohort and casecontrol studies). In college‐age athletes, postconcussion syndrome is predicted by previous concussion and symptoms such as amnesia, poor concentration, photophobia, and insomnia at presentation (SOR: B, case‐control study).